Synthesis of 4-tosyl quinazoline derivatives with the assistance of ultrasound irradiation as a guide to the reaction pathway - Manijeh Nematpour (Scientific Reports)
Abstract In this study, we tried to show the role of ultrasonic waves in the reaction pathway of quinazolines with an amide functional group. At first, 4-tosyl quinazolines were prepared using a simple, rapid, and one-pot reaction of Cu-catalyzed cross-coupling reactions of 2-iodoaniline and tosyl methyl isocyanide (TosMIC) in THF solvent under ultrasonic conditions in 30 min with good efficiency. The role of ultrasound in this reaction is to reduce the time and increase the efficiency of product preparation. Then, considering the potential of some synthesized derivatives to carry out the cross-coupling reaction with the help of isocyanides, copper iodide catalyst, and cesium carbonate as a base in THF solvent was investigated. Spectroscopic evidence1H-NMR,13C-NMR, IR, and Mass) shows interesting results that the reaction proceeds under ultrasonic conditions towards C–H activation and without the use of ultrasonic towards cross-coupling reaction. Finally, 22 new heterocyclic compounds from the 4-tosylquinazoline family have been synthesized under ultrasonic conditions in this project with a simple, rapid, and efficient method.